PENCEGAHAN KEKERASAN SEKSUAL REM PENCEGAHAN KEKERASAN SEKSUAL REMAJA PADA MODEL PEMBELAJARAN FIQIH KONTEKSTUAL: Penelitian di MTs Al-Fathaniyah Serang, Banten - Itoh Masitoh Masitoh; Muhajir Muhajir; Hasbullah Hasbullah; Teguh Fachmi; Ade Adriadi (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
The objectives of the research are sex education material in fiqh lessons and efforts to prevent adolescent sexual violence through contextual fiqh learning models. Descriptive qualitative research design, the object of research for class VII students. Primary data: head of madrasa, waka for student affairs and curriculum, teachers, students. Secondary data: books, journals, articles. Instruments of observation, documentation, interviews, FGD. Data analysis techniques are data reduction, data display, inference and verification. The result of the research is that the taharah material includes the procedures for taking a janabah bath, the characteristics of puberty, menstruation and using the Safinatun Nazah book. As well as MA XI's fiqh adultery material. Also material harassment and sexual violence. Efforts to prevent adolescent sexual violence are carried out by teaching material on fiqh taharah, adultery which is included in sex education material using a contextual approach. And it has a negative impact on the perpetrators in terms of religion, medical, social, and at MTs Al-Fathaniyah there is a PIK-R training that focuses on discussing health in adolescence. The conclusion of the study is that there is a prevention solution through sex education materials in fiqh subjects.